Familiarity of objects affects susceptibility to the sound-induced flash illusion - SETTI, ANNALISA (Elsevier, 2011)
Audition is accepted as more reliable (thus dominant) than vision when temporal discrimination is required by the task. However, it is not known whether the characteristics of the visual stimulus, for example its familiarity to the perceiver, affect auditory dominance. In this study we manipulated familiarity of the visual stimulus in a well-established multisensory phenomenon, i.e. the sound-induced flash illusion. This illusion occurs when, for example, one brief visual stimulus (e.g. a flash) is presented in close temporal proximity with two brief sounds; participants perceive two flashes instead of one. We found that when the visual faces or buildings stimuli were familiar, participants were less susceptible to the illusion than when they were unfamiliar. As the illusion has been ascribed to early cross-sensory interactions between vision and audition, the present work offers behavioural evidence that high level processing of objects? characteristics such as familiarity, affect early temporal multisensory integration. Possible mechanisms underlying the effect of familiarity are discussed.
PUBLISHED
Keywords: Neuroscience; auditory dominance; multisensory integration